Humanization of Mathematics Pedagogy Amid the Expansion of Intelligent Technology - Baharuddin (International journal of technology and education research, 2026)
The expansion of intelligent technologies, especially Artificial Intelligence (AI), has changed mathematics education through adaptive learning systems, learning analytics, and intelligent tutoring systems. While many studies show improvements in efficiency and short-term cognitive outcomes, these technologies do not always ensure meaningful and reflective learning that supports holistic human development. This study aims to review and synthesize recent literature on the humanization of mathematics pedagogy in the era of intelligent technologies, and to develop a conceptual framework that positions technology as a partner, not a replacement, for teachers. A systematic literature review (SLR) was conducted using 10 articles published between 2023 and 2025 from reputable databases. The analysis followed stages of identification, selection, eligibility, and thematic synthesis to integrate empirical findings, humanistic theories, and ethical perspectives. The results show that AI-based mathematics learning is still largely technocentric, focusing on personalization and performance. However, recent studies emphasize the importance of human-AI collaboration, ethical use, and the development of social-emotional aspects in learning. Humanizing mathematics pedagogy requires viewing technology as a tool that supports dialogue, empathy, metacognition, and conceptual understanding. This study offers a conceptual framework for humanizing mathematics pedagogy in the digital era, along with theoretical, practical, and policy implications for AI integration in education. Overall, the findings highlight the need to design technology-based learning that remains grounded in human values, ensuring that digital transformation aligns with the core goals of education.